'It's all about patient safety': an ethnographic study of how pharmacy staff construct medicines safety in the context of polypharmacy. Issue 2 (5th February 2021) - Fudge, Nina; Swinglehurst, Deborah
Abstract : Objective: As polypharmacy increases, so does the complexity of prescribing, dispensing and consuming medicines. Medication safety is typically framed as the avoidance of harm, achievable through adherence to policies, guidelines and operational standards. Automation, robotics and technologies are positioned as key players in the elimination of medication error in the face of escalating demand, despite limited research illuminating how these innovations are taken up, used and adapted in practice. We explore how 'safety' is constructed and accomplished in community pharmacies in the context of polypharmacy. Design and setting: In-depth ethnographic case study across four community pharmacies in England (December 2017–July 2019). Data collection entailed 140 hours participant observation and 19 in-depth interviews. Practice theory informed the analysis. Participants: 33 pharmacy staff (counter staff, technicians, dispensers, pharmacists). Results: In their working practices related to polypharmacy, staff used the term 'safety' in explanations of why and how they were doing things in particular ways. We present three interlinked analytic themes within an overarching narrative of care: caring for the technology; caring for each other; and caring for the patient. Our study revealed a paradox: polypharmacy was visible, pervasive and productive of numerous routines, but rarely discussed as a safety concern per se. Safety meant ensuring medicines were dispensed as prescribed, and correcting errors pertaining to individual drugs through the clinical check. Pharmacy staff did not actively challenge polypharmacy, even when the volume of medicines dispensed might indicate 'high risk' polypharmacy, locating the responsibility for polypharmacy with prescribing clinicians. Conclusion: 'Safety' in the performance of practices relating to polypharmacy was not a fixed, defined notion, but an ongoing, collaborative accomplishment, emerging within an organisational narrative of 'care'. Despite meticulous attention to 'safety', carefully guarded professional boundaries meant that addressing polypharmacy per se in the context of community pharmacy was beyond reach.